Directional multipolehght transport model for rendering translucent materials - Pomalaya, Diana Estefania Naranjo (2017)
Translucent materials, such as milk or marble, are characterized by their soft and smooth appear- ance, as well as their bleed through effect when illuminated from behind. Diffusion based models are currently the best approximation of the real physical process that takes place underneath the surface of this kind of material. This process, dubbed subsurface scattering, is the one one respon- sible for the blurring effect that generates that soft appearance. The success of these models is due to the similarity between energy and light propagation. Since diffusion theory solves the problem of energy propagation, its use returns a good approximation of subsurface scattering. Aiming to produce a better approximation for translucent materials we developed an extension of a diffusion based subsurface scattering model called directional multipole. In our model we extend the directional dipole to achieve a better solution for thin slabs, i.e. shallow depths. The directional dipole is a model that uses a diffusion theory solution for a ray in an infinite medium, which comes closer to the representation of light rays since they have a magnitude and a direction. This is what differentiates it from the other diffusion based models, which are based on a solution for a point in an infinite medium. This model, however, fails to represent thin slabs because it assumes light steps are infinitely smaller than the depth of the object. Our model solves this problem by merging the directional dipole model with the multipole model, which was the first and only model that addresses this issue. By doing this, we created a model that achieves a closer approximation to the real for thin slabs than those of the multipole.